Encouraging robust oil spill planning, preparedness, and response in Chesterfield Inlet, Nunavut, Canada - Adams, Ashley (2025)
Area-based oil spill plans such as community oil spill plans are essential for Arctic regions. The outcome of this project is the creation of a series of policy briefing notes based on consideration of Canadian policy and programs alongside those in Arctic jurisdictions outside of Canada. The project’s objective was aimed at “creating a policy brief on oil spill planning, preparedness, and response for Canadian Arctic communities”. Given the results of the document and literature review, the briefing notes focused on the following areas: Background Area Information, Monitoring Regimes, Training Regimes, Local Involvement Requirements, and Framework for a Community Oil Spill Response Company. Recommendations in each of these areas are applicable to the Canadian Eastern Arctic community context. Some of the project’s main findings include the use of background information as a reference point/resource to inform area-based monitoring and training regimes. Regarding local involvement, it is suggested that a community advisory council/board would promote community-led oil spill planning, preparedness, and response tasks, such as risk assessments and knowledge exchange (oil spill response experience). A regional oil spill response company should be established that emphasizes community to community agreements (based on a hub structure). This would require ship/vessel owners to enter into response agreements with the company. The detailed briefing notes and recommendations are focused on local involvement and will help to inform Arctic communities, such as Chesterfield Inlet, and all levels of government about actions that are essential to improve the oil spill planning, preparedness, and response capabilities. May 2025